Mencari Kartika [videorecordings] a documentary film. - Kaprawi, Norhayati (Lensa Srikandi, 2010)
This documentary film explores the Muslim's perception of "justice" in the context of Malaysia that is lauded for its moderm, progressive, multi-racial image. Kartika herself has endorsed the film, saying that it offers viewers a larger truth about her actions and statements after she has sentenced.